2022
DOI: 10.1101/2022.03.25.485808
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Cellular Taxonomy of the Adult Human Spinal Cord

Abstract: In neurodegenerative diseases of the human spinal cord, such as amyotrophic lateral sclerosis (ALS), motoneurons are particularly vulnerable to degeneration. It is hypothesized that their large size contributes to disease susceptibility, but the link between genetic variants associated with disease and cell-type specific degeneration is not clear. We characterized human spinal cord cells using single-nucleus RNA-sequencing and protein profiling. We found that human motoneurons displayed a unique expression pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 106 publications
2
15
0
Order By: Relevance
“…Although in most CNS regions PV-expressing neurons are inhibitory, the dorsal horn represents a unique area in which the calcium buffer is also expressed in excitatory neurons (Häring et al, 2018; Sathyamurthy et al, 2018, Russ et al, 2021). This feature is not restricted to mice, as recent data from rhesus macaque (Arokiaraj et al, 2022) and human (Yadav et al, 2022) dorsal horns indicate that PV is expressed in both glutamatergic and GABAergic neuronal clusters. The percentage of excitatory and inhibitory neurons expressing PV has been studied in mice and is less consistent, varying from 50 to 95% inhibitory (Hughes et al, 2012; Petitjean et al, 2015; Abraira et al, 2017; Gradwell et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although in most CNS regions PV-expressing neurons are inhibitory, the dorsal horn represents a unique area in which the calcium buffer is also expressed in excitatory neurons (Häring et al, 2018; Sathyamurthy et al, 2018, Russ et al, 2021). This feature is not restricted to mice, as recent data from rhesus macaque (Arokiaraj et al, 2022) and human (Yadav et al, 2022) dorsal horns indicate that PV is expressed in both glutamatergic and GABAergic neuronal clusters. The percentage of excitatory and inhibitory neurons expressing PV has been studied in mice and is less consistent, varying from 50 to 95% inhibitory (Hughes et al, 2012; Petitjean et al, 2015; Abraira et al, 2017; Gradwell et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…Recent advances in ISH and IHC on human spinal cord tissue (Shiers et al, 2021; Yadav et al, 2022; Arokiaraj et al, 2022; Dedek et al, 2022) provide the needed resources that will help validate our preclinical findings of inhibitory neurons. In the mouse, the dorsal horn is comprised of several subsets of inhibitory interneurons involved in modality-specific processing of peripheral inputs (Bourane et al, 2015a; Bourane et al, 2015b; Koch et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, a similar integrative approach was used to create a harmonized atlas of mouse spinal cord cell types, but with limited details of OLs ( Russ et al, 2021 ). Lastly, a comprehensive cellular taxonomy of the adult human spinal cord was recently released by Yadav et al (2022) , including an integrative analysis of mouse and human data.…”
Section: Oligodendrocyte Heterogeneity In Healthmentioning
confidence: 99%
“…While this work was in progress, a single cell RNA seq analysis was performed on seven lumbar spinal cords with some of the cases included in the present article and aged 50-80 years old. Results are released as a preprint manuscript and an associated browsable interface 22 . Using this gene expression database, we found that 6/7 of the genes we explored in our study by IHC, namely Arx, FoxJ1, Msx1, Pax6, Rfx2 and Sox2 were well expressed in ependymal cells at the single cell RNA level (fig.…”
Section: Resultsmentioning
confidence: 99%